Removal of Methylene Blue from Aqueous Solution by Non-Living Biomass of Marine Algae and Freshwater Macrophyte - Xue Song Wang; Ying Zhou; Yu Jiang (Adsorption Science & Technology)
The adsorption of Methylene Blue, a Basic dye, onto the nonliving biomass of marine algae and freshwater macrophyte was investigated by batch experiments. Such adsorption onto both adsorbents was pH-independent. The experimental data were analyzed using pseudo-first-order and pseudo-second-order kinetic equations, the results suggesting that the data were described well by both models. Intraparticle diffusion played an important role in the mass-transfer process. Methylene Blue adsorption onto both adsorbents at 20°C was also evaluated by the Freundich and Langmuir isotherms. The maximum adsorption capacities were 155.31 mg/g for Laminaria japonica (LJ) biomass and 150.39 mg/g for alligator weed (AW) biomass, respectively. The effects of adsorbent concentration and ionic strength on Methylene Blue adsorption were also investigated. The adsorbents investigated could serve as low-cost adsorbents for removing Methylene Blue from aqueous solution.